SISTEM INFORMASI PENENTUAN SISWA BERPRESTASI DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (Studi Kasus : MTs Terpadu Riyadul Badiah) - Erik Kurniadi (Cloud Information, 2016)
The process of determining qualified student is a process of assessing the best students from various aspects determined by the school. Determining best students in MTs Terpadu Riyadul Badiyah is very important to improve the students’ enthusiasm for learning, because the award will motivate student’s learning achievement. Determining fast and accurate calculations needs a system that can handle the management of decision-making to produce the best students. Simple Additive weighting method (SAW) is a method that can be used to determine students’ achievement. The case study is done at MTs Terpadu Riyadul Badiyah. There are five criteria that will be used as reference for determining student achievement that is the average value, the value of the English language, the value of the activity, the value of personality and value of attendance. The greatest value will produce the qualified student. Information System for Determining qualified Student is expected to be used as tools in MTsTerpadu Riyadul Badiyah. With this system, the school can easily choose the criteria and determine the best student at the school. Keywords: Information Systems, Students, Achievement, Decision Support Systems, SAW, PHP, MySql